Barriers of the internationalization in smes in transition countries: evidence and methodological suggestion in case of Mongolia - Altnaa, Ulziimaa; Neszmélyi, György Iván (Studia Mundi – Economica, 2021)
Globally, Small and Medium-Sized Enterprises (SMEs) have been recognized as pivotal contributors to the country’s economy. The main goal of this paper is to investigate country specific barriers to the internationalization process in SMEs in the transition country’s context. SMEs in transition countries deal with the common challenges that are usually occurred in other economies as well and they also have to overcome challenges of institutional external and internal barriers during their internationalization. We set and suggest a mixed-method research design to explore barriers to the SMEs' internationalization phenomenon in transition countries from various perspectives using diverse approaches as Mongolia as a case. By this paper, we can contribute to the narrow existing literature in the field of the internationalization of SMEs in the transition countries by investigating SMEs in Mongolia so as to provide implications to researchers, practitioners, policymakers, and SME owners or managers.